Performance Characterization Of Micro Porous Media Burner For Heat Or Power Generation - Janvekar, Ayub Ahmed (2019)
The threat of fossil fuel depletion affects the nation’s economy. Consequently, attempts are made to improve the use of fuels by developing highly efficient burners. With this intention, present work was focused to develop premixed butane based micro porous media burner. The burner was designed to undergo surface and submerged flames by varying equivalence ratio. Two types of reaction layer were tested; foam and ball type porous media (PM), while porcelain foam in preheat zone. Thickness of reaction and preheat layer was varied suitably to get optimum burner performance. Thus 90% thermal efficiency was noted by using 15 mm alumina foam along with 10 mm porcelain foam. Values of NOx and CO at optimum equivalence ratio was less than 15 and 60 ppm respectively. Further, 4% improvement in the thermal efficiency was achieved by adding 80 μL of vegetable oil droplets over reaction layer. In addition, electric power of 2.018 W was generated from the surface flame using TE cells. These TE cells are integrated to a hybrid configuration, it includes circuit fan powered from solar panels. Moreover, height between reaction layer and TE cells was optimized (69 mm) using design of experiments to further increase electric power by 8%. Finally, three dimensional numerical study was performed to compare experimental data for both temperature and emissions (NOx and CO) at a critical equivalence ratio (ER=0.7)